HDAC1 is required for GATA-1 transcription activity, global chromatin occupancy and hematopoiesis. Issue 17 (27th August 2021) - Yan, Bowen; Yang, Jennifer; Kim, Min Young; Luo, Huacheng; Cesari, Nicholas; Yang, Tao; Strouboulis, John; Zhang, Jiwang; Hardison, Ross; Huang, Suming; Qiu, Yi
Abstract: The activity of hematopoietic factor GATA-1 is modulated through p300/CBP-mediated acetylation and FOG-1 mediated indirect interaction with HDAC1/2 containing NuRD complex. Although GATA-1 acetylation is implicated in GATA-1 activation, the role of deacetylation is not studied. Here, we found that the FOG-1/NuRD does not deacetylate GATA-1. However, HDAC1/2 can directly bind and deacetylate GATA-1. Two arginine residues within the GATA-1 linker region mediates direct interaction with HDAC1. The arginine to alanine mutation (2RA) blocks GATA-1 deacetylation and fails to induce erythroid differentiation. Gene expression profiling and ChIP-seq analysis further demonstrate the importance of GATA-1 deacetylation for gene activation and chromatin recruitment. GATA-1 2RA knock-in (KI) mice suffer mild anemia and thrombocytopenia with accumulation of immature erythrocytes and megakaryocytes in bone marrow and spleen. Single cell RNA-seq analysis of Lin − cKit + (LK) cells further reveal a profound change in cell subpopulations and signature gene expression patterns in HSC, myeloid progenitors, and erythroid/megakaryocyte clusters in KI mice. Thus, GATA-1 deacetylation and its interaction with HDAC1 modulates GATA-1 chromatin binding and transcriptional activity that control erythroid/megakaryocyte commitment and differentiation.